Important forgotten earthquakes for Medellin (2014)
The aim of this little paper is to disseminate between regional geoscientists an historical data about an earthquake or swarm of earthquakes, felt in what is now the city of Medellín, in 1730. As far as is known, this event has not been reported before in available historical catalogs. It is important to understand the seismic hazard of the city and the region. An brief analysis is made with the limited published historical information.